The Reflection on Some Questions Concerning the Introduction to the Subject of Theological Symposium “Ontology and Ethics” (2003) - Пауновић, Томислав (Sabornost - The Theological Year-book, 2015)
Twelve years after the symposium which raised the issue of relation between Ontology and Ethics within the Church, there is a need to continue with developing the subject. It is not in a favor of the fact that we were the witnesses of massive criticism by the formal theological public, against the subject. We afraid that these reactions indicate the unwillingness of Christian thought for a wrestling with issues of paramount importance for the future history of Christendom in the world. Instead of continuation of serious theological dialogue on the subject, initiated at symposium Ontology and Ethics (Požarevac, 2003), we met with condemnation of the very idea for developing the topic which is almost prohibited, but surely rejected. In this article we try to make a modest contribution to further development of the topic. It is not only that the ethical concept of Church is in crisis due of dealing with new challenges of history of the Church, but it is intrinsically faulty model which doesn’t express the Church on the right way and threatens to transform its traditional mode of existence. The Church is an event or the happening of the Communion; existing in the Communion; living in the Communion. As such, she is the Mysterious “Model” through which God saves the world; through which there is a transfiguration of actual and unsustainable ontology of created world, in the ontology of God, who is the Communion, that is Trinity. Newer streams in human thought in general may be of great help on this matter, and names of Heidegger, Leivnas and Buber are outstanding within them. So, in the most of the article we are dealing with Levinas’ thought, who can be regarded as a prophet of Ethics of The New Age. Conversely, the Church is ontological reality.